Respon Pertumbuhan dan Produksi Beberapa Kultivar Padi Gogo Lokal Sultra Terhadap Volume pemberian Air - Borromeu, Moizes dos Reis; Sadimantara, I Gusti Rai; Pasolon, Yulius B. (Universitas Halu Oleo, 2018)
ABSTRACT The purpose of the study was to find out the respond growth and production of local upland rice Sultra’s on the watering volume. The research was conducted in green house sized 4x10 m, from April to August 2015. This study tested four (4) cultivation local upland rice Sultra in the pot and treated with sub-optimum and optimal water levels of 25%, 50%, 100% and 150%. The experiment was conducted by using factorial desing of two factors of randoming complete block design (RCBD) with three replications, where first factor is W (water level) is comprised of four levels; W1 (25%), W2 (50%), W3 (100%), and W4 (150%). Second factor is cultivars upland rice local comprised of four levels; V1 (cultivar pae dai Ngalaru), V2 (cultivar pae Uba), V3 (cultivar pae Bou) and V4 (cultivar pae Bandoeha). The parameter observed were t plant height of the number of maximum tiller, number of leave, dry weight, dry weight of root, number of productive tiller, days to flowering, weight of 1000 rice, number of grain per tiller, the percentage of empty grain per tiller (%), blossoming age, and number of dry grain per tree.There is an interaction influence of water volume 100% and cultivation of pae dai Ngalaru to the height to the plant 70 days after planting and cultivating pae Bou to the tiller 70 days after the planting, 50% of water volume and cultivar of pae Uba to the number of the leaves 70 days after the planting, 25 % water conditions and cultivar pae Bou to empty grain per plant. The effect of dependent water 100% (W3) gave the good result on the averages of grain per tree to various cultivar of upland rice, water conditions 100% (W3) gave the best results on the averages of dry weight of the root of 70 days after planting, water conditions 25% (W1) and cultivar pae Uba (V2) is the longest type average of grain to blossom. The effect of dependent cultivar of pae Uba (V2) gave good result on the averages of dry weight of peak of plant 70 HST, cultivar pae Bou (V3) gave good result on the averages of number of productive tiller, cultivar of pae Bandoeha (V4) gave good result on the averages of weight of grain seed 1000, cultivar pae Bou (V3) gave good result on the averages of grain per tree.Keywords: Upland Rice, Volume Water, Growth and Production